Men of today, soyboys of tomorrow: Constructions of masculinities in YouTube responses to Gillette's The Best Men Can Be. (October 2022) - Iveson, Mandie; Formato, Federica
Abstract: In this article, we investigate, through corpus linguistics and qualitative approaches, YouTube responses to an advert which attempts to bring to the fore detrimental masculine toxic behaviours. With the affordances proper to the medium - anonymity, disinhibition, and de-individuation - our investigation focuses on three gendered terms representing subordinate masculinities (Messerschmidt, 2018): soy, cuck and beta, challenging 'masculine' attributes such as toughness, power, heterosexuality, competitiveness, and authority. These are thought to deviate from alpha masculinity between traditional opposite points: alpha men and women. The findings show that compound identities are also constructed, and deviant and subordinate masculinities are seen to be associated with political or social movements. Furthermore, comments suggest that traditional masculinity is threatened by groups of men who are considered socially inferior, provoking a (white) male sense of nostalgic entitlement. This online platform becomes a mediated space for discrimination, a softer manosphere, where anti-feminist sentiments are implicit. This article contributes to the literature on discourse and masculinities, and constructions of gender in online hostile spaces.